2017
DOI: 10.3390/rs9080861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Small-Scale Gold Mining Tailings on the Underwater Light Field in the Tapajós River Basin, Brazilian Amazon

Abstract: Artisanal and Small-scale Gold Mining (ASGM) within the Amazon region has created several environmental impacts, such as mercury contamination and changes in water quality due to increased siltation. This paper describes the effects of water siltation on the underwater light environment of rivers under different levels of gold mining activities in the Tapajós River Basin. Furthermore, it investigates possible impacts on the phytoplankton community. Two field campaigns were conducted in the Tapajós River Basin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
(94 reference statements)
0
15
0
5
Order By: Relevance
“…Increased water siltation has a strong impact and direct consequences for how light is attenuated in the water and consequently the depth of the euphotic zone. For instance, Lobo et al [41] have defined that in the Tapajós River basin, the euphotic zone can decrease from 6.0 m to 1.0 m in non-impacted and ASGM impacted rivers, respectively. These changes can potentially change the phytoplankton community [41], and primary production [42].…”
Section: Spatio-temporal Analysiof Asgm and Water Siltation (1973-2012)mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased water siltation has a strong impact and direct consequences for how light is attenuated in the water and consequently the depth of the euphotic zone. For instance, Lobo et al [41] have defined that in the Tapajós River basin, the euphotic zone can decrease from 6.0 m to 1.0 m in non-impacted and ASGM impacted rivers, respectively. These changes can potentially change the phytoplankton community [41], and primary production [42].…”
Section: Spatio-temporal Analysiof Asgm and Water Siltation (1973-2012)mentioning
confidence: 99%
“…With regards to ASGM, the consequences of water siltation to the aquatic environment, more specifically, to underwater light field and phytoplankton production, have been evaluated by [41]. In short, strong light attenuation reduces euphotic zone from 6 m to, approximately, 1 m in non-impacted and impacted water bodies, which can potentially change the phytoplankton community and decrease the photic zone and, thus, primary production.…”
Section: Management Recommendations and Future Researchmentioning
confidence: 99%
“…In addition to the direct use for SSGM controlling and monitoring by these national agencies, the applicability of these products for aquatic research is enormous. In fact, evaluation of light attenuation caused by mining tailing has shown that, in general, the euphotic zone in impacted rivers has decreased to at least half of nonimpacted rivers [36]. Several studies can use TSS distribution as an input for hydrological and sediment transportation models; studies on light attenuation and consequences to the biota, as well as socioeconomic studies, will benefit from this research.…”
Section: Future Researchmentioning
confidence: 99%
“…Industrial iron mining in Carajás, for example, applies high-end technology throughout the whole process of surveying, exploiting, and recovering the area, resulting in high yields with minimum environmental impacts. On the other hand, small-scale gold mining in the Tapajós River, for example, uses low-end technology in ore processing (water jets and dredges) with low yields and high impact levels on land degradation and water contamination (sediment and mercury) [14][15][16][17].…”
Section: Mining Sites In the Brazilian Amazonmentioning
confidence: 99%